ANALISIS FAKTOR RISIKO TERJADINYA HIPERTENSI PADA IBU HAMIL - Ni Kadek Tias Tanti; Titin Dewi Sartika Silaban (Poltekkes Kemenkes Medan, 2022)
The maternal mortality rate is still very high, where every 2 minutes somewhere in the world, a woman dies due to pregnancy complications. Efforts to reduce MMR include an early pregnancy detection program by carrying out a standard pregnancy check-up with 8 visits. One of the causes of pregnancy complications is hypertension. This study aims to determine the relationship between age, gravidity, family history of hypertension, and BMI with the incidence of hypertension in pregnant women. This study uses a quantitative type of research using an analytic survey design, namely a cross-sectional population of all pregnant women who check their pregnancy, the sample in this study amounted to 34 respondents with the sampling technique using the Accidental Sampling technique. Data collection was obtained by using a questionnaire, statistical tests using the chi-square test. The results of this study indicate that 26 respondents suffer from hypertension (76.5%) and 8 people do not suffer from hypertension (23.5%). The results of statistical tests showed that there was a relationship between age (p=0.002) and an OR of 23.3. There was a relationship between gravity (p=0.003) and an OR of 10. There was a relationship between a family history of hypertension (p=0.014) and an OR of 13.22. There is a relationship between BMI (p=0.009). It can be concluded that there is a relationship between age, gravidity, family history of hypertension, and BMI with the incidence of hypertension in pregnant women. Suggestions for Puskesmas should be formed a team of health extension workers to increase knowledge of pregnant women regarding risk factors for hypertension to minimize complications in pregnancy.